Mendobrak Pola Konvensional Pengembangan Kewirausahaan Di Era Industri 4.0: Peningkatan Peranan Perguruan Tinggi Melalui Inkubator Bisnis Dan Teknologi - Muhamad Ariza Eka Yusendra; Melda Agarina, Susanti, Hendra Kurniawan, Lilla Rahmawati, Niken Paramitasari (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2019)
To survive in the 4.0 industry era, everyone in business must be able to develop contemporary, digital based business models to achieve the highest level of efficiency and the best quality of products. However, many stakeholders still choose to go the conventional way with business models that are not designed to adapt to 4.0 business environment. The solution to this gap could possibly be higher education involvement as agents of change and knowledge resource to upgrade micro, small, and medium enterprises. The purpose of this community service programme was to do just that through business incubator organisations and technology by implementing Integrated Incubation System based on creative economy on cases in IBI Darmajaya. The method used was a combination of observation, interview, consultation, workshop, mentoring, coaching, and utilising new technologies. This community service programme involved partners from various business segments such as culinary entrepreneurs, appropriate technology, digital startupreneur, and student academics. This programme resulted in the partners’ newfound skill of developing contemporary business models for 4.0 industry and an increase in production, sales, profit, and business scale.